POTRET PENDIDIKAN: ANTARA PENDIDIKAN, GLOBALISASI, DAN KAPITALISME - Faizal Alifiandi (IAIN Purwokerto, 2018)
Abstract: The world system, which is currently in the global-capitalist phase, makes everything change so quickly. This cannot be denied because of the rapid growth of world technology and information. The rapid change has entered the realm of education. The reality shows that education has now begun to lose its main function, which is to form a whole person / humanize humans. Education is still a fairly steep gap between the owners of capital and the marginalized. The views on certification and accreditation also need to be clarified that this is not a manifestation of what is learned from education. Certification and accreditation are only part of educational instruments that cannot be used as the main reference in assessing what is obtained after going through the education process. Furthermore, bank-style education must also be eliminated because it is the most obvious form of castration of humans’ intellectual potential. Bank style education should be transformed into enlightening education, which is a practice where students are truly placed in the position of active subjects, not as passive objects that can be arbitrarily suppressed by their educators. Keywords: education, globalization, and capitalism.